Magnetic resonance imaging arthrography following type II superior labrum from anterior to posterior repair: interobserver and intraobserver reliability - Kurji HM; Ono Y; Nelson AA; More KD; Wong B; Dyke C; Boorman RS; Thornton GM; Lo IK (Open Access Journal of Sports Medicine, 2015)
Hafeez M Kurji,1 Yohei Ono,2,3 Atiba A Nelson,2 Kristie D More,2 Ben Wong,4 Corinne Dyke,4 Richard S Boorman,2 Gail M Thornton,2,5 Ian KY Lo2 1College of Medicine, University of Saskatchewan, Saskatoon, SK, Canada; 2Department of Surgery, Section of Orthopaedic Surgery, McCaig Institute for Bone and Joint Health, University of Calgary, Calgary, AB, Canada; 3Department of Orthopedic Surgery, Nagoya University Graduate School of Medicine, Nagoya, Japan; 4Department of Radiology, University of Calgary, Calgary, AB, Canada; 5Department of Orthopaedics, University of British Columbia, Vancouver, BC, Canada Background: Arthroscopic repair of type II superior labrum from anterior to posterior (SLAP) lesions is a common surgical procedure. However, anatomic healing following repair has rarely been investigated. The intraobserver and interobserver reliability of magnetic resonance imaging arthrography (MRA) following type II SLAP repair has not previously been investigated. This is of particular interest due to recent reports of poor clinical results following type II SLAP lesion repair. Purpose: To evaluate the MRA findings following arthroscopic type II SLAP lesion repair and determine its intraobserver and interobserver reliability. Study design: Cohort study (diagnosis), Level of Evidence, 2. Methods: Twenty-five patients with an isolated type II SLAP lesion (confirmed via diagnostic arthroscopy) underwent standard suture anchor-based repair. At a mean of 25.2 months postoperatively, patients underwent a standardized MRA protocol to investigate the integrity of the repair. MRAs were independently reviewed by two radiologists and a fellowship trained shoulder surgeon. The outcomes were classified as healed SLAP repair or re-torn SLAP repair. Results: On average, 54% of MRAs were interpreted as healed SLAP repairs while 46% of MRAs were interpreted as having a re-torn SLAP repair. Overall, only 43% of the studies had 100% agreement across all interpretations. The intraobserver reliability ranged from 0.71 to 0.81 while the interobserver reliability between readers ranged from 0.13 to 0.44 (Table 1). Conclusion: The intraobserver agreement of MRA in the evaluation of type II SLAP repair was substantial to excellent. However, the interobserver agreement of MRA was poor to fair. As a result, the routine use of MRA in the evaluation of type II SLAP lesion repair should be utilized with caution. A global evaluation of the patient, including detailed history and physical examination, is paramount in determining the cause of failure and one should not rely on MRA alone. Keywords: SLAP, MRA, labrum, postoperative